Navigating Mixed Identities in Colonized Nations: Exploring Self-Apprehension Through Post-Colonial Lens - Kanwal, Attia; Ashfaq, Tayyeba (Pakistan Languages and Humanities Review, 2024)
The study aims to examine the use of self-apprehension processes to study the values and reject conventional colonial rhetoric. Three poets, Langston Hughes from Africa, Oodegeroo Noonuccal from Australia, and Shujta Bhatt from India have their post-colonial perspectives examined in this qualitative study. With an emphasis on nationhood and nationalism, the writers seek to rewrite history for their countries. Hughes’ "The Negro Speaks of Rivers" describes the rich cultural legacy of the African race, Noonuccal’s "The Dispossessed" symbolizes the wrongs done to her country by European colonists, and Bhatt’s "A Different History" examines the effects of colonialism on the Indian people. According to Ashcroft’s national and regional models, the distinctive features of the particular national or regional culture are explored. The realities of colonized and colonizers are brought to light in post-colonial literature, emphasizing how colonizers’ seeds have weakened the foundations of colonized nations and destroyed their sense of national identity. By highlighting the cultural and moral distinctions between colonized and colonizers, the research opens the ground for further researchers to explore the problem of reputation and dignity through a colonial lens.